Pelatihan Pembuatan Desinfektan Bagi Kader Posyandu - Islawati, Islawati; Jumrah, Elfira; Yunus, Muhammad; Alimin, Alimin; Salnus, Subakir (Universitas Negeri Gorontalo, 2025)
The increasing demand for disinfectants to maintain environmental hygiene and prevent the spread of diseases in Paenre Lompoe Village, Bulukumba Regency, poses a challenge for Posyandu cadres who have limited knowledge and access to disinfectant products. To address this issue, disinfectant production training was conducted to empower Posyandu cadres to produce disinfectants independently. This activity involved 20 cadres using a participatory approach, including theory, demonstrations, and hands-on practice. Evaluations through pre-tests and post-tests showed an increase in participants' understanding from 30% to 85%, along with the successful production of 10 liters of ready-to-use disinfectant. The main challenges faced in this training included time constraints and the need for additional equipment for larger-scale production. The advantages of this activity lie in the use of easily accessible local materials and the active involvement of participants. Moving forward, this training presents opportunities for developing small-scale businesses based on disinfectant production, which has the potential to improve the economic well-being of the cadres’ families. The results of this training demonstrate that a holistic approach can enhance the capacity of Posyandu cadres in supporting community health independently and sustainably.